Time-Restricted Feeding and Aerobic Performance in Elite Runners: Ramadan Fasting as a Model - Al-Nawaiseh, Ali M.; Bataineh, Mo'ath F.; Kilani, Hashem A.; Bellar, David M.; Judge, Lawrence W. (Frontiers in Nutrition, 2021)
A distance runner’s performance is generally limited by energy availability when competing or training. Modifying meal frequency and timing by abstaining from eating or drinking, from dawn to dusk, during Ramadan fasting is hypothesized to induce hypohydration and reduced caloric and nutrient intake. The purpose of this study was to investigate the impact of Ramadan fasting on runners’ performances. Fifteen trained male distance runners who observed Ramadan participated in this study (Age = 23.9 ± 3.1 years; Peak VO2= 71.1 ± 3.4 ml/kg/min). Each participant reported to the human performance lab on two testing occasions (pre-Ramadan and the last week of Ramadan). In each visit, participants performed a graded exercise test on the treadmill (Conconi protocol) and their VO2, Heart Rate, time to exhaustion, RPE, and running speed were recorded. Detailed anthropometrics, food records, and exercise logs were kept for the entire period of the study. Repeated measure ANOVA, paired t-test, and Cohen’s effect size analysis were carried out. Results indicated no significant influence for Ramadan fasting on body mass (p=0.201), body fat (p=0.488), lean body mass (p=0.525), VO2max (p=0.960), energy availability (p=0.137), and protein intake (p=0.124). However, carbohydrate (p=0.026), lipid (p=0.009), water (p<0.001), and caloric intakes (p=0.002) were significantly reduced during Ramadan Fasting. Daily training duration (p < 0.001) and exercise energy expenditure (p= 0.001) were also reduced after Ramadan. Time to exhaustion (p= 0.049), and maximal running speed (p=0.048) were improved. Overall, time to exhaustion and maximal running speed of the distance runners was improved during Ramadan fasting, independent of changes in nutrients intake observed during the current study. With proper modulation of training, distance runner’s performance can be maintained or even slightly improved following the month of Ramadan fasting.